Preparation method of polydextrose water-soluble dietary fiber

Through the multi-stage filtration technology of ceramic membranes and modified composite membranes, combined with modified TiO2 and sulfonate methacrylate treatment, the problems of membrane pollution and poor temperature resistance in traditional polyglucose preparation are solved, and efficient and environmentally friendly polyglucose water-soluble dietary fiber production is achieved, improving product quality and production efficiency.

CN120424249APending Publication Date: 2025-08-05RUNLOY BIOTECH SHANGHAI CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510562644.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-30
Publication Date
2025-08-05

AI Technical Summary

Technical Problem

In the traditional polyglucose preparation method, there are problems such as high production costs, high energy consumption, serious membrane pollution, and short membrane life. Especially the poor temperature resistance of commercially available ultrafiltration membranes, which affects production efficiency and product quality.

Method used

Multi-stage filtration was performed using ceramic membrane and modified composite membrane, combined with modified TiO2 and sulfonate methacrylate treatment, and the modified composite membrane was prepared. By precisely controlling the reaction conditions and filtration parameters, the photocatalytic characteristics and hydrophilicity of modified TiO2 were used to improve the film's anti-pollution ability and water solubility.

Benefits of technology

It realizes efficient and environmentally friendly polyglucose water-soluble dietary fiber production, reduces production costs, improves product purity and stability, extends the service life of the membrane, and improves water solubility and anti-pollution performance.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to a preparation method of polydextrose water-soluble dietary fiber, and belongs to the technical field of food. According to the preparation method disclosed by the invention, reaction conversion of glucose, sorbitol and citric acid is effectively promoted by accurately regulating and controlling reaction conditions, and the product purity is improved by utilizing a multi-stage filtering technology. Polyether sulfone and polyvinylidene fluoride are adopted as main components of the membrane, and modified TiO2 is added, so that the anti-pollution capacity and the photocatalytic characteristic of the membrane are remarkably enhanced. In addition, the hydrophilicity and the anti-pollution performance of the membrane are further improved through treatment and irradiation curing of sulfobetaine methacrylate. The preparation method not only improves the production efficiency, but also ensures the high quality and safety of the product, provides a high-quality dietary fiber source for the fields of food, health care products and the like, and shows remarkable advantages in the aspects of environmental protection and efficient production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of food and relates to a method for preparing polydextrose water-soluble dietary fiber. Background Art

[0002] Polydextrose is a polysaccharide derived from glucose, a natural corn derivative. It is low in calories and has a low glycemic index, while also serving as both a water-soluble dietary fiber and a prebiotic. As a functional food ingredient, polydextrose has demonstrated significant benefits in regulating intestinal function, enhancing immunity, promoting mineral absorption, lowering blood sugar, and managing weight. As people pursue healthier diets, polydextrose is finding increasing application in food, health supplements, and pharmaceuticals.

[0003] Traditional polydextrose production methods primarily rely on acid hydrolysis, which converts glucose into gluconic acid using an acid catalyst. Polydextrose is then produced through enzymatic hydrolysis, polymerization, purification, and drying. However, this method has significant drawbacks: The traditional acid hydrolysis process requires multiple alcohol precipitation and purification steps to remove impurities. This not only increases solvent consumption and production costs during production, but also poses a significant environmental burden due to the wastewater treatment generated during the alcohol precipitation and purification process. Furthermore, ultrafiltration membrane technology is a common separation method used in polydextrose purification. However, commercially available ultrafiltration membranes generally have poor temperature tolerance and require operation at relatively low temperatures. This not only limits the temperature range during production and increases cooling energy consumption, but also easily leads to severe membrane fouling, which affects throughput. Due to the poor temperature tolerance of commercially available ultrafiltration membranes, they are susceptible to fouling due to factors such as operating conditions and feed composition. Membrane fouling not only significantly reduces throughput but also shortens membrane life and increases replacement costs. Summary of the Invention

[0004] The invention aims to provide a method for preparing polydextrose water-soluble dietary fiber, which has the characteristics of good water solubility and low reducing sugar content.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] A method for preparing polydextrose water-soluble dietary fiber, the specific steps of the preparation method are as follows:

[0007] S1-1: Glucose, sorbitol, and citric acid were mixed and placed in a vacuum reactor. The reactor was heated to 140°C at 5°C / min and maintained for 30 min, then heated to 170°C at 2°C / min and maintained for 2 h. The vacuum degree was set to -0.08 MPa to obtain a reaction solution.

[0008] S1-2: The reaction solution is filtered through a ceramic membrane at a temperature of 120°C and a pressure of 0.8 MPa to obtain a primary filtrate;

[0009] S1-3: Decolorize the first-stage filtrate. The amount of decolorizer added is 3% to 5% of the mass of the first-stage filtrate. The decolorization temperature is 100 to 110°C, the contact time is 40 to 60 minutes, and the circulation pump flow rate is 0.5m 3 / h;

[0010] S1-4: The decolorized filtrate is filtered through a modified composite membrane for secondary filtration at a temperature of 100-110°C and a pressure of 1.2 MPa;

[0011] S1-5: The secondary filtrate is concentrated, dried and pulverized to obtain the polydextrose water-soluble dietary fiber.

[0012] As a preferred technical solution of the present invention, the glucose, sorbitol and citric acid in S1-1 are mixed in a mass ratio of (80-90): (10-20): (1-3).

[0013] As a preferred technical solution of the present invention, the particle size of the ceramic membrane in S1-2 is 200 nm, and the material of the ceramic membrane is one of ZrO2 and Al2O3.

[0014] As a preferred technical solution of the present invention, the decolorizing agent in S1-3 is one of activated carbon and white clay.

[0015] As a preferred technical solution of the present invention, the preparation method of the modified composite membrane in S1-4 is as follows:

[0016] S5-1: polyethersulfone and polyvinylidene fluoride were mixed in a mass ratio of 7:3, ultrasonicated for 10 to 30 minutes, and 3 to 5 wt% of modified TiO2 was added to prepare a base film by a phase inversion method at 25°C;

[0017] S5-2: Immersing the base film in a 0.5% by mass sulfobetaine methacrylate solution for 8 to 10 hours, and then irradiating it with 60Coγ rays at a dose of 25 kGy to obtain the modified composite film.

[0018] As a preferred technical solution of the present invention, the preparation method of the modified TiO2 is:

[0019] S6-1: Cellulose nanofibers were added to deionized water to form a 1 wt% suspension, sonicated for 2–3 h, and then freeze-dried at -30°C for 12–16 h to obtain a nanofiber template.

[0020] S6-2: Tetrabutyl titanate, urea, and silver nitrate were mixed and dissolved in a 50% ethanol solution, and the nanofiber template was added. The mixture was immersed at 80°C for 24 hours, and then calcined at 600°C for 2 hours under a nitrogen atmosphere, and then reduced under ultraviolet light for 1-2 hours.

[0021] S6-3: Add the reduced substance to a polylactic acid solution with a mass fraction of 10-20%, stir at a speed of 550-750 r / min at 40-46°C for 1-2 hours, wash with deionized water and place it at 60°C under vacuum and dry for 10-14 hours to obtain the modified TiO2.

[0022] As a preferred technical solution of the present invention, the coagulation bath of the phase inversion method in S5-1 is a 40% DMF aqueous solution.

[0023] As a preferred technical solution of the present invention, the tetrabutyl titanate, urea and silver nitrate in the S6-2 are mixed in a molar ratio of 10:0.5:0.01.

[0024] As a preferred technical solution of the present invention, the wavelength of the ultraviolet light in S6-2 is 365nm.

[0025] As a preferred technical solution of the present invention, the S1-5 is concentrated to a solid content of 40-60%, and dried under vacuum at 50-70° C. to a moisture content of ≤5%.

[0026] The preparation method of the present invention realizes an efficient and environmentally friendly production process through a series of finely controlled steps. First, the method effectively promotes the reaction conversion of glucose, sorbitol and citric acid by precisely controlling the reaction temperature, vacuum degree and filtration conditions. At the same time, multi-stage filtration is performed using ceramic membranes and modified composite membranes to effectively remove impurities and improve the purity of the product. The decolorization treatment further improves the color quality of the product, making it more in line with market demand. Finally, through concentration, drying and pulverization, a polydextrose water-soluble dietary fiber that is easy to use and store is obtained. The method of the present invention not only improves production efficiency, but also ensures the high quality and safety of the product, providing a high-quality source of dietary fiber for the fields of food, health products, etc.

[0027] This invention uses polyethersulfone and polyvinylidene fluoride as the primary membrane materials, with a mass ratio of 7:3. This ratio effectively balances the mechanical strength, chemical stability, and permeability of the base membrane. Polyethersulfone, with its excellent mechanical strength and chemical stability, provides a solid backbone for the base membrane, while polyvinylidene fluoride, with its excellent solvent resistance and permeability, adds flexibility to the membrane material. Furthermore, the addition of modified TiO2 further enhances the versatility of the composite membrane.

[0028] In the preparation of modified TiO2, natural cellulose nanofibers are used as a guiding structure to promote the growth of titanium dioxide into a composite material with a three-dimensional porous network structure, significantly increasing the material's specific surface area and providing more active sites for photocatalytic reactions. Simultaneously, a co-doping strategy with nitrogen and silver effectively narrows the band gap of TiO2, enabling the composite material to undergo photocatalytic reactions under visible light irradiation. Nitrogen doping not only adjusts the electronic structure of TiO2 but also enhances its absorption capacity for visible light, thereby improving photocatalytic efficiency. Under light conditions, TiO2 can be excited to generate electron-hole pairs, which in turn trigger a series of chemical reactions that decompose organic pollutants into harmless substances. This process not only maintains the unobstructed pores of the membrane but also significantly extends the membrane's service life, ensuring its high efficiency and stability during long-term operation. The introduction of silver, through the formation of silver nanoparticles, not only further enhances the material's photocatalytic activity but also imparts excellent antibacterial properties. These Ag NPs are uniformly loaded onto the TiO2 surface via a photoreduction method, demonstrating a potent and long-lasting antibacterial capacity with an inhibition rate exceeding 99% against harmful microorganisms such as Escherichia coli. Furthermore, the three-dimensional porous network design imparts excellent anti-fouling properties to the composite material. This porous structure not only facilitates the rapid diffusion and adsorption of pollutants but also effectively reduces clogging of the membrane surface by pollutants, thereby significantly improving water flux. Polylactic acid (PLA) coating significantly enhances the compatibility of the modified TiO2 with polyethersulfone (PES) and polyvinylidene fluoride (PVDF). As a biocompatible and degradable polymer, PLA's surface functional groups, such as hydroxyl and carboxyl groups, interact with functional groups in the polymer matrix, enhancing interfacial bonding. Furthermore, the PLA coating effectively reduces agglomeration of the modified TiO2 particles, improving their uniform dispersion within the polymer matrix. It also further stabilizes the Ag NPs, preventing them from shedding or agglomerating during processing or use.

[0029] The base membrane is treated with sulfobetaine methacrylate and cured by 60Co gamma-ray irradiation, imparting excellent hydrophilicity and anti-fouling properties to the composite membrane. The introduction of a zwitterionic polymer forms a dense hydrophilic layer on the membrane surface, effectively preventing the adsorption and deposition of contaminants such as proteins and microorganisms, thereby ensuring efficient, long-term, and stable operation of the membrane.

[0030] In addition, the modified composite membrane also exhibits good thermal stability and chemical corrosion resistance, and can maintain its structural integrity and stable performance in various harsh environments, which helps to ensure the separation efficiency and product quality during the preparation of polydextrose water-soluble dietary fiber.

[0031] Beneficial effects of the present invention:

[0032] (1) The present invention combines polyethersulfone and polyvinylidene fluoride and optimizes the ratio to 7:3, thereby achieving a balance between the mechanical strength, chemical stability and permeability of the base membrane. The addition of modified TiO2, with its unique surface properties and chemical activity, significantly enhances the anti-pollution ability of the composite membrane and gives it photocatalytic properties, effectively decomposing organic pollutants and extending the life of the membrane. In addition, the treatment with sulfobetaine methacrylate and 60Coγ-ray irradiation curing further enhance the hydrophilicity and anti-pollution properties of the membrane, forming a dense hydrophilic layer to prevent the adsorption of pollutants. The modified composite membrane also has good thermal stability and chemical corrosion resistance, ensuring efficient and stable operation under various environments, which is crucial to improving the preparation efficiency and product quality of polydextrose water-soluble dietary fiber.

[0033] (2) The bio-template method is used to utilize natural cellulose nanofibers to guide titanium dioxide to form a three-dimensional porous network structure. Combined with the co-doping of nitrogen and silver elements and the loading of silver nanoparticles, the specific surface area is significantly increased and the band gap is narrowed, achieving efficient visible light catalytic degradation of organic residues in the polydextrose process, while enhancing long-term antibacterial and anti-pollution capabilities and improving water flux. In addition, the surface of the modified TiO2 is coated with a thin layer of polylactic acid, which can effectively promote the close bonding between the modified TiO2 and the polymer matrix and improve its dispersion uniformity in the polymer matrix. DETAILED DESCRIPTION

[0034] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined purpose of the invention, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.

[0035] Example 1

[0036] A method for preparing polydextrose water-soluble dietary fiber, the specific steps of the preparation method are as follows:

[0037] S1-1: Glucose, sorbitol, and citric acid were mixed in a mass ratio of 85:15:2 in a vacuum reactor. The reactor was heated to 140°C at a rate of 5°C / min and maintained for 30 min, then heated to 170°C at a rate of 2°C / min and maintained for 2 h. The vacuum degree was set to -0.08 MPa to obtain a reaction solution.

[0038] S1-2: The reaction solution is filtered through a ZrO2 ceramic membrane with a particle size of 200 nm at a filtration temperature of 120°C and a pressure of 0.8 MPa to obtain a primary filtrate;

[0039] S1-3: Decolorize the first-stage filtrate. The amount of activated carbon added is 4% of the mass of the first-stage filtrate. The decolorization temperature is 105°C, the contact time is 50 minutes, and the circulation pump flow rate is 0.5m 3 / h;

[0040] S1-4: The decolorized filtrate is filtered through a modified composite membrane for secondary filtration at a temperature of 105°C and a pressure of 1.2 MPa;

[0041] S1-5: The secondary filtrate is concentrated, dried and pulverized respectively, wherein the concentration is performed to a solid content of 50%, and the drying is performed at 60° C. under vacuum and dried to a moisture content of ≤5% to obtain the polydextrose water-soluble dietary fiber.

[0042] The preparation method of the modified composite membrane in S1-4 is as follows:

[0043] S5-1: Polyethersulfone and polyvinylidene fluoride were mixed in a mass ratio of 7:3, ultrasonicated for 20 minutes, and 4 wt% modified TiO2 was added. The base membrane was prepared by phase inversion at 25°C. The coagulation bath was a 40% DMF aqueous solution.

[0044] S5-2: Immersing the base film in a 0.5% by mass sulfobetaine methacrylate solution for 9 hours, and then irradiating it with 60Coγ rays at a dose of 25 kGy to obtain the modified composite film.

[0045] The preparation method of the modified TiO2 is:

[0046] S6-1: Cellulose nanofibers were added to deionized water to form a 1 wt% suspension, sonicated for 2.5 h, and then freeze-dried at -30 °C for 14 h to obtain a nanofiber template;

[0047] S6-2: Tetrabutyl titanate, urea, and silver nitrate were mixed in a molar ratio of 10:0.5:0.01 and dissolved in a 50% ethanol solution. The nanofiber template was added and immersed at 80°C for 24 hours. The mixture was then calcined at 600°C for 2 hours under a nitrogen atmosphere and then reduced under ultraviolet light at a wavelength of 365 nm for 1.5 hours.

[0048] S6-3: The reduced substance was added to a 15% by mass polylactic acid solution, stirred at 43°C at a speed of 650 r / min for 1.5 h, washed with deionized water and placed under vacuum drying at 60°C for 12 h to obtain the modified TiO2.

[0049] Example 2

[0050] A method for preparing polydextrose water-soluble dietary fiber, the specific steps of the preparation method are as follows:

[0051] S1-1: Glucose, sorbitol, and citric acid were mixed in a mass ratio of 80:10:1 in a vacuum reactor. The reactor was heated to 140°C at a rate of 5°C / min and maintained for 30 min, then heated to 170°C at a rate of 2°C / min and maintained for 2 h. The vacuum degree was set to -0.08 MPa to obtain a reaction solution.

[0052] S1-2: The reaction solution is filtered through an Al2O3 ceramic membrane with a particle size of 200 nm at a filtration temperature of 120°C and a pressure of 0.8 MPa to obtain a primary filtrate;

[0053] S1-3: Decolorize the primary filtrate. The amount of white clay added is 3% of the mass of the primary filtrate. The decolorization temperature is 100°C, the contact time is 40 minutes, and the circulation pump flow rate is 0.5m 3 / h;

[0054] S1-4: The decolorized filtrate is filtered through a modified composite membrane for secondary filtration at a temperature of 100°C and a pressure of 1.2 MPa;

[0055] S1-5: The secondary filtrate is concentrated, dried and pulverized respectively, wherein the concentration is performed to a solid content of 40%, and the drying is performed at 50° C. under vacuum and dried to a moisture content of ≤5% to obtain the polydextrose water-soluble dietary fiber.

[0056] The preparation method of the modified composite membrane in S1-4 is as follows:

[0057] S5-1: Polyethersulfone and polyvinylidene fluoride were mixed in a mass ratio of 7:3, ultrasonicated for 10 minutes, and 3 wt% of modified TiO2 was added. The base membrane was prepared by phase inversion at 25°C. The coagulation bath was a 40% DMF aqueous solution.

[0058] S5-2: Immerse the base film in a 0.5% by mass sulfobetaine methacrylate solution for 8 hours, and then irradiate it with 60Coγ rays at a dose of 25 kGy to obtain the modified composite film.

[0059] The preparation method of the modified TiO2 is:

[0060] S6-1: Cellulose nanofibers were added to deionized water to form a 1 wt% suspension, sonicated for 2 h, and then freeze-dried at -30 °C for 12 h to obtain a nanofiber template;

[0061] S6-2: Tetrabutyl titanate, urea, and silver nitrate were mixed in a molar ratio of 10:0.5:0.01 and dissolved in a 50% ethanol solution. The nanofiber template was added and immersed at 80°C for 24 hours. The mixture was then calcined at 600°C for 2 hours under a nitrogen atmosphere and then reduced under ultraviolet light at a wavelength of 365 nm for 1 hour.

[0062] S6-3: adding the reduced substance to a 10% by mass polylactic acid solution, stirring at 40°C and 550 r / min for 1 hour, washing with deionized water and vacuum drying at 60°C for 10 hours to obtain the modified TiO2.

[0063] Example 3

[0064] A method for preparing polydextrose water-soluble dietary fiber, the specific steps of the preparation method are as follows:

[0065] S1-1: Glucose, sorbitol, and citric acid were mixed in a mass ratio of 90:20:3 in a vacuum reactor. The reactor was heated to 140°C at a rate of 5°C / min and maintained for 30 min, then heated to 170°C at a rate of 2°C / min and maintained for 2 h. The vacuum degree was set to -0.08 MPa to obtain a reaction solution.

[0066] S1-2: The reaction solution is filtered through a ZrO2 ceramic membrane with a particle size of 200 nm at a filtration temperature of 120°C and a pressure of 0.8 MPa to obtain a primary filtrate;

[0067] S1-3: Decolorize the first-stage filtrate. The amount of activated carbon added is 5% of the mass of the first-stage filtrate. The decolorization temperature is 110°C, the contact time is 60 minutes, and the circulation pump flow rate is 0.5m 3 / h;

[0068] S1-4: The decolorized filtrate is filtered through a modified composite membrane at a secondary filtration temperature of 110°C and a pressure of 1.2 MPa;

[0069] S1-5: The secondary filtrate is concentrated, dried and pulverized respectively, wherein the concentration is performed to a solid content of 60%, and the drying is performed at 70° C. under vacuum and dried to a moisture content of ≤5% to obtain the polydextrose water-soluble dietary fiber.

[0070] The preparation method of the modified composite membrane in S1-4 is as follows:

[0071] S5-1: Polyethersulfone and polyvinylidene fluoride were mixed in a mass ratio of 7:3, ultrasonicated for 30 minutes, and 5 wt% modified TiO2 was added. The base membrane was prepared by phase inversion at 25°C. The coagulation bath was a 40% DMF aqueous solution.

[0072] S5-2: Immersing the base film in a 0.5% by mass sulfobetaine methacrylate solution for 10 hours, and then irradiating it with 60Coγ rays at a dose of 25 kGy to obtain the modified composite film.

[0073] The preparation method of the modified TiO2 is:

[0074] S6-1: Cellulose nanofibers were added to deionized water to form a 1 wt% suspension, sonicated for 3 h, and then freeze-dried at -30 °C for 16 h to obtain a nanofiber template;

[0075] S6-2: Tetrabutyl titanate, urea, and silver nitrate were mixed in a molar ratio of 10:0.5:0.01 and dissolved in a 50% ethanol solution. The nanofiber template was added and immersed at 80°C for 24 hours. The mixture was then calcined at 600°C for 2 hours under a nitrogen atmosphere and then reduced under ultraviolet light at a wavelength of 365 nm for 2 hours.

[0076] S6-3: adding the reduced substance to a 20% by mass polylactic acid solution, stirring at 750 r / min at 46° C. for 2 h, washing with deionized water and vacuum drying at 60° C. for 14 h to obtain the modified TiO 2 .

[0077] Comparative Example 1

[0078] Steps S1-4 are omitted, and the remaining steps are the same as those in Example 1.

[0079] Comparative Example 2

[0080] No modified TiO2 was added during the preparation of the modified composite membrane, and the remaining steps were the same as those in Example 1.

[0081] Comparative Example 3

[0082] Commercially available TiO2 was added during the preparation of the modified composite membrane, and the remaining steps were the same as those in Example 1.

[0083] Commercially available TiO2 was purchased from Shanghai Yien Chemical Technology Co., Ltd. with a purity of 99%.

[0084] Comparative Example 4

[0085] The preparation of modified TiO2 does not include step S6-3, and the remaining steps are the same as those in Example 1.

[0086] Comparative Example 5

[0087] The preparation of the modified composite membrane does not include step S5-2, and the remaining steps are the same as those in Example 1.

[0088] The relevant parameters of the polydextrose water-soluble dietary fibers prepared in the examples and comparative examples are summarized in the following table.

[0089] Solubility Reducing sugar content Example 1 excellent 0.4% Example 2 excellent 0.5% Example 3 excellent 0.4% Comparative Example 1 good 3.6% Comparative Example 2 excellent 1.8% Comparative Example 3 excellent 2.7% Comparative Example 4 excellent 2.1% Comparative Example 5 excellent 1.1%

[0090] It can be seen from the data of the examples and comparative examples that the polydextrose water-soluble dietary fiber obtained by the preparation method of the present invention has excellent water solubility and extremely low reducing sugar content.

[0091] The above description is merely a preferred embodiment of the present invention and does not constitute any form of limitation to the present invention. Although the present invention has been disclosed as a preferred embodiment as above, it is not intended to limit the present invention. Any person skilled in the art can make some changes or modifications to equivalent embodiments using the technical contents disclosed above without departing from the scope of the technical solution of the present invention. However, any simple modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A method for preparing polydextrose water-soluble dietary fiber, characterized in that: The specific steps of the preparation method are as follows: S1-1: Glucose, sorbitol, and citric acid were mixed and placed in a vacuum reactor. The reactor was heated to 140°C at 5°C / min and maintained for 30 min, then heated to 170°C at 2°C / min and maintained for 2 h. The vacuum degree was set to -0.08 MPa to obtain a reaction solution. S1-2: The reaction solution is filtered through a ceramic membrane at a temperature of 120°C and a pressure of 0.8 MPa to obtain a primary filtrate; S1-3: Decolorize the first-stage filtrate. The amount of decolorizer added is 3% to 5% of the mass of the first-stage filtrate. The decolorization temperature is 100 to 110°C, the contact time is 40 to 60 minutes, and the circulation pump flow rate is 0.5m 3 / h; S1-4: The decolorized filtrate is filtered through a modified composite membrane for secondary filtration at a temperature of 100-110°C and a pressure of 1.2 MPa; S1-5: The secondary filtrate is concentrated, dried and pulverized to obtain the polydextrose water-soluble dietary fiber.

2. The method for preparing a polydextrose water-soluble dietary fiber according to claim 1, wherein: In the S1-1, glucose, sorbitol and citric acid are mixed in a mass ratio of (80-90):(10-20):(1-3).

3. The method for preparing a polydextrose water-soluble dietary fiber according to claim 1, wherein: The particle size of the ceramic membrane in S1-2 is 200 nm, and the material of the ceramic membrane is one of ZrO2 and Al2O3.

4. The method for preparing a polydextrose water-soluble dietary fiber according to claim 1, wherein: The decolorizing agent in S1-3 is one of activated carbon and white clay.

5. The method for preparing a polydextrose water-soluble dietary fiber according to claim 1, wherein: The preparation method of the modified composite membrane in S1-4 is as follows: S5-1: polyethersulfone and polyvinylidene fluoride were mixed in a mass ratio of 7:3, ultrasonicated for 10 to 30 minutes, and 3 to 5 wt% of modified TiO2 was added to prepare a base film by a phase inversion method at 25°C; S5-2: Immersing the base film in a 0.5% by mass sulfobetaine methacrylate solution for 8 to 10 hours, and then irradiating it with 60Coγ rays at a dose of 25 kGy to obtain the modified composite film.

6. The method for preparing polydextrose water-soluble dietary fiber according to claim 5, wherein: The preparation method of the modified TiO2 is: S6-1: Cellulose nanofibers were added to deionized water to form a 1 wt% suspension, sonicated for 2–3 h, and then freeze-dried at -30°C for 12–16 h to obtain a nanofiber template. S6-2: Tetrabutyl titanate, urea, and silver nitrate were mixed and dissolved in a 50% ethanol solution, and the nanofiber template was added. The mixture was immersed at 80°C for 24 hours, and then calcined at 600°C for 2 hours under a nitrogen atmosphere, and then reduced under ultraviolet light for 1-2 hours. S6-3: Add the reduced substance to a polylactic acid solution with a mass fraction of 10-20%, stir at a speed of 550-750 r / min at 40-46°C for 1-2 hours, wash with deionized water and place it at 60°C under vacuum and dry for 10-14 hours to obtain the modified TiO2.

7. The method for preparing a polydextrose water-soluble dietary fiber according to claim 5, characterized in that: The coagulation bath of the phase inversion method in S5-1 is a 40% DMF aqueous solution.

8. The method for preparing polydextrose water-soluble dietary fiber according to claim 6, wherein: In the S6-2, tetrabutyl titanate, urea and silver nitrate are mixed in a molar ratio of 10:0.5:0.

01.

9. The method for preparing polydextrose water-soluble dietary fiber according to claim 6, wherein: The wavelength of the ultraviolet light in S6-2 is 365 nm.

10. The method for preparing polydextrose water-soluble dietary fiber according to claim 1, characterized in that: The S1-5 is concentrated to a solid content of 40-60%, and dried under vacuum at 50-70° C. to a moisture content of ≤5%.